Uji Efektifitas Ekstrak Etanol Bawang Batak terhadap Keputihan yang Berlebihan pada Wanita Usia Subur - Iskandar Markus Sembiring; Novidawati Boru Situmorang (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
Batak onion plants contains flavonoids, triterpenoids, steroids, and saponins. Compounds that can inhibit bacterial growth are flavonoids. This type of research is a quantitative study using a true experimental research design (pure experiment) with a rancangan “pretest-posttes“ model. Namely, before the treatment was carried out, observations were made on the sample and after the treatment was also carried out several observations. Collecting samples, making simplicia, making extraction by maceration using 96% ethanol solvent, making thick extracts with concentrations of 15%, 20% and 25%. The effectiveness test was carried out in reducing excessive vaginal discharge by taking the vaginal discharge for women of childbearing age, then doing a pH test on the vaginal discharge and adding the ethanol extract of batak onions after that the pH test was again carried out. The results showed that the onion extract (Allium schoenoprasum L) concentrations of 15%, 20% and 25% were able to reduce excessive vaginal discharge in women of childbearing age and the results of vaginal pH examinations showed that the concentration of 25% was faster to stabilize vaginal pH which was too alkaline. For further researchers, it is recommended to formulate the ethanol extract of the onion hobo (Allium schoenoprasum L) into a solid soap or ovule preparation.